Evaluation of 0.6% sodium alginate as a submucosal injection material in endoscopic submucosal dissection for early gastric cancer. Issue 5 (24th March 2014) - Kusano, Toru; Etoh, Tsuyoshi; Akagi, Tomonori; Ueda, Yoshitake; Shiroshita, Hidefumi; Yasuda, Kazuhiro; Satoh, Masahiro; Inomata, Masafumi; Shiraishi, Norio; Kitano, Seigo
<x xml:space="preserve">Abstract</x> Background and Aim We have focused on sodium alginate (SA) solution as a potential submucosal injection material for endoscopic submucosal dissection (ESD). A previous SA solution had high viscosity and problems such as difficult handling. After its properties were adjusted, SA solution was examined in vitro and its clinical safety was evaluated. Methods With 0.4% sodium hyaluronate (SH) solution as a control, catheter injectability and mucosa‐elevating capacity of 0.3–0.8% SA solutions were evaluated. Next, 0.6% SA solution was used for ESD in 10 patients with early gastric cancer in a prospective clinical study. Results Compared with 0.4% SH solution, 0.6% SA solution exhibited no significant difference in catheter injectability but significant superiority in mucosa‐elevating capacity. In the clinical study, no adverse events were observed in any patient. Conclusion The safety of 0.6% SA solution as a submucosal injection material was confirmed and it is suggested that its efficacy should be investigated in a larger number of cases.